Metagenomic next-generation sequencing to investigate infectious keratitis by Corynespora cassiicola: a case report - Shuo Xu; Shui Lu; Yan Gu; Hongjuan Sun; Minghui Ma; Yue Leng; Wenhui Liu (Frontiers in Medicine, 2023)
In this report, the case of a 65-year-old immunosuppressed female who presented with recurring redness and irritation in her right eye for 2 months is described. Ocular examination revealed conjunctival congestion, feather-like greyish-white corneal deep stromal infiltrate, white, floccular material sprawling from the anterior chamber angle and hypopyon. The in vivo confocal microscopy (IVCM) instantly confirmed fungal keratitis, and empirical antifungal therapy was thus administered. The patient exhibited therapeutic penetrating keratoplasty, however, due to the progression of infection and the lack of identified pathogens. The fungal isolate was identified as Corynespora cassiicola by metagenomic next-generation sequencing (mNGS) of the host cornea. The patient responded well to intensive conservative therapy and subsequent surgical therapy. To our knowledge, this case represents the first case of C. cassiicola infection from China, highlighting the emergence of a rare fungus that causes keratitis. Furthermore, mNGS has the capability to facilitate prompt identification and timely management of challenging ocular infections that are difficult to diagnose.